Training after the Achilles tendon injury in a volleyball player - 2014 to 2020, part 2. (Origina) (Revista científica Olimpia, 2024)
The objective of the study was to present how was structured the periodization of a volleyball player in the Achilles tendon injury from 2014 to 2018. The subject of the study was a volleyball player that was of the study of Marques Junior and Barbosa (2016). The specific periodization for volleyball was developed for a volleyball player that had a partial rupture of the Achilles tendon in 2014. In the period from 2014 to 2016, the training load gradually increased to avoid new injuries to this anatomical region. The volleyball player began the jumping with both legs in 2016. In 2017 and 2018, the plyometric training had a greater training load and other types of training followed this procedure. In conclusion, periodized training allows that the athlete to safely increase the training load gradually after a partial rupture in the Achilles tendon.
Keywords: injury; sport; rupture; tendon; training